1997
DOI: 10.1073/pnas.94.26.14776
|View full text |Cite
|
Sign up to set email alerts
|

Targeted deletion of all isoforms of the trkC gene suggests the use of alternate receptors by its ligand neurotrophin-3 in neuronal development and implicates trkC in normal cardiogenesis

Abstract: We have generated null mutant mice that lack expression of all isoforms encoded by the trkC locus. These mice display a behavioral phenotype characterized by a loss of proprioceptive neurons. Neuronal counts of sensory ganglia in the trkC mutant mice reveal less severe losses than those in NT-3 null mutant mice, strongly suggesting that NT-3, in vivo, may signal through receptors other than trkC. Mice lacking either NT-3 or all trkC receptor isoforms die in the early postnatal period. Histological examination … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
140
0

Year Published

1999
1999
2010
2010

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 186 publications
(149 citation statements)
references
References 57 publications
9
140
0
Order By: Relevance
“…Similarly, inactivation of either TrkB or brain-derived neurotrophic factor results in an equivalent loss of mechanoceptive neurons (Ernfors et al, 1994;Minichiello et al, 1995). On the other hand, neonates invalidated for TrkC present a loss of 30% DRG neurons, whereas NT-3 À/À neonates have lost 70% of them (Tessarollo et al, 1994(Tessarollo et al, , 1997. This is in agreement with the view that TrkC, contrary to TrkA and B, can trigger, when deprived of ligand, an active apoptotic signaling.…”
Section: Role Of Drs During Embryonic Developmentsupporting
confidence: 86%
“…Similarly, inactivation of either TrkB or brain-derived neurotrophic factor results in an equivalent loss of mechanoceptive neurons (Ernfors et al, 1994;Minichiello et al, 1995). On the other hand, neonates invalidated for TrkC present a loss of 30% DRG neurons, whereas NT-3 À/À neonates have lost 70% of them (Tessarollo et al, 1994(Tessarollo et al, , 1997. This is in agreement with the view that TrkC, contrary to TrkA and B, can trigger, when deprived of ligand, an active apoptotic signaling.…”
Section: Role Of Drs During Embryonic Developmentsupporting
confidence: 86%
“…First, mRor2 is required for cardiac septal formation. Recent genetic analyses have revealed that many regulatory molecules, including growth factors, receptors and transcription factors, are involved in the development of the heart (Nagasawa et al 1996;Basson et al 1997;Li et al 1997;Tessarollo et al 1997;de la Pompa et al 1998;Ranger et al 1998;Schott et al 1998;Tachibana et al 1998; reviewed in Burn & Goodship 1996;Lyons 1996;Rossant 1996;Barinaga 1998), although in general their roles are not restricted to septal formation. Interestingly, defects of the cardiac septum have been, thus far, the major abnormality observed in the cardio-vascular system of mRor2 À/À mice.…”
Section: Discussionmentioning
confidence: 99%
“…So far, the reason for the discrepancy between our work and the report by Cronk et al (2002) remains elusive. The TrkC null mouse line (Tessarollo et al, 1997), the stage of development, and the location in which Merkel cell differentiation was monitored, the whisker follicle, were the same in both studies. One difference lies in the Merkel cell markers that have been used.…”
Section: Discussionmentioning
confidence: 99%
“…TrkC heterozygous mice (Tessarollo et al, 1997) were maintained on a C57BL/6 inbred background. Homozygous mutant mice do not express any TrkC protein (Tessarollo et al, 1997).…”
Section: Experimental Procedures Animalsmentioning
confidence: 99%
See 1 more Smart Citation